Sistem informasi penjualan dan pemesanan import barang berbasis web PT Bumi Jaya - Rahmatullah, Dwi Fany; Syidada, Shofiya (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
PT. Bumi Jaya is a company with an import business of various building and other materials. On In this company, transactions for ordering imported goods are still carried out manually by employees. The stages of the imported goods process are after the customer places an order for imported goods from the company will create PIB documents (Notification of Imported Goods), SPPB (Letter of Approval for Release of Goods), and DO (delivery order) for travel documents so that orders for imported goods can reach customers. This research aims to design and build an information system for importing goods that is useful for making things easier employees and customers to transact. From the test results, this system has an automatic generation feature PIB documents, simplify the process of importing goods, directors can quickly access sales information company, and sales files become safer and take up less space because they use files digital. This system is expected to be useful for company administration transactions and reports sales PT. Bumi Jaya is more effective and efficient.